Race and gender inequalities in the brazilian economic and cultural relations - Grubba, Leilane Serratine (2022)
The research focuses on race and gender intersectional inequalities in the context of Brazilian economic and cultural relations. It starts from the coloniality of power in the constitution of race and gender, in order to analyze, as the main objective, how inequalities were historically constituted through a cultural and economic distinction project. The research problem is: how the Brazilian economic and social system uses racialized people, specially black women? We use the complexity method. The research contributes to the field by highlighting political alternatives to articulate equality and identity, to restructuct social organization and guarantee a equal coexistence for gender, class and race, aiming at the deconstruction of the coloniality of power and economic and social redistribution.